Implementation of Deep Learning based on Local Wisdom 'Bhineka Tunggal Ika, Tan Hana Dharma Mangrwa' in MI Central Java: An Ethnographic Study of Education - Musslifah, Anniez Rachmawati; Cale Deporos, Saprolla Rollie; Purnomosidi, Faqih (Institut Agama Islam Daruttaqwa Gresik, 2025)
This research aims to explore the implementation of deep learning based on the local wisdom of Bhineka Tunggal Ika and Tan Hana Dharma Mangrwa in the context of learning at Madrasah Ibtidaiyah (MI) Elementary Islamic School Central Java. This study aims to analyze how the multicultural values and diversity contained in the Javanese philosophy are integrated into deep learning approaches to strengthen students’ character education. The research uses an ethnographic approach to schooling with data collection methods through participatory observation, in-depth interviews with teachers and students, and analysis of curriculum documents. The research location was chosen in three MIs in Central Java that implement learning based on local wisdom. The study results show that deep learning has become an effective medium for transforming the values of Bhineka Tunggal Ika into learning activities, primarily through collaborative projects, interactive discussions, and digital content developed by teachers. However, the main challenge lies in the limitations of technological infrastructure and the need for teacher training in designing AI-based materials. This study provides recommendations in the form of a deep learning-local wisdom integration model that is adaptive to the socio-cultural context of MI while emphasizing the importance of strengthening teacher capacity in 21st-century learning.